Investigation of hydrogen adsorption-absorption into thin palladium films. I. Theory - GABRIELLI, C; GRAND, P. P; LASIA, A; PERROT, H (Journal of the Electrochemical Society, 2004)
Models of insertion of hydrogen in metal films coating a gold electrode are presented in terms of faradaic impedance. They take into account adsorption of the protons from the solution on the electrode surface (two-step mechanism) or direct absorption in the metal (one-step mechanism) and diffusion in the metal. In addition, trapping of the hydrogen atoms and direct exchange of the trapped hydrogen with the solution are considered. The main feature discussed here is the change of the charge-transfer resistance with the thickness of the metal film. This surprising behavior is related to the exchange reaction of trapped hydrogen with the solution. The impedance diagrams are calculated for a palladium film both in the underpotential deposited (UPD) domain and the hydrogen evolution domain. In the UPD domain an impedance of the ion-blocking electrode is found. In the hydrogen evolution domain two capacitive loops are found for a film whose thickness is less than 1 micrometer.